Odontogenic infection involving the secondary fascial space in diabetic and non-diabetic patients: a clinical comparative study - Chang, Je-Shin; Yoo, Kil-Hwa; Yoon, Sung Hwan; Ha, Jiwon; Jung, Seunggon; Kook, Min-Suk; Park, Hong-Ju; Ryu, Sun-Youl; Oh, Hee-Kyun (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2013)
This retrospective study was performed to evaluate the clinical impact of diabetes mellitus on the prognosis in secondary space infection. Medical records, radiographic images, computed tomography, and microbial studies of 51 patients (25 diabetic patients and 26 non-diabetic patients) were reviewed. Patients were diagnosed as secondary fascial space infections with odontogenic origin and underwent treatment at Chonnam National University Hospital, in Department of Oral and Maxillofacial Surgery, from January 2007 to February 2009. COMPARED TO PATIENTS WITHOUT DIABETES, PATIENTS WITH DIABETES WERE PRESENTED WITH THE FOLLOWING CHARACTERISTICS: older age (diabetic patients: 62.9 years, non-diabetic patients, 47.8 years), more spaces involved (diabetic patients, 60%; non-diabetic patients, 27.3%), more intense treatment, longer hospitalization (diabetic patients, 28.9 days; non-diabetic patients, 15.4 days), higher white blood cell and C-reactive protein values, higher incidence of complication (diabetic patients, 40%; non-diabetic patients, 7.7%), and distinctive main causative microorganisms. These results suggest that the prognosis of diabetic patients is poorer than that of non-diabetic patients in secondary space infections since they had greater incidence rates of involved spaces, abnormal hematologic findings, more complications, and additional procedures, such as tracheostomy.